The ocean is a bridge, not a chasm - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The shared ocean ISBN 92 828 3186 8, 1998. Published by the European Commission, Directorate-General for Development Information Unit Rue de la Loi 200 B 1049 Brussels Belgium Fax: +32 2 299 3002 Website: http://europa.eu.int/